2015
DOI: 10.1039/c4cp04538f
|View full text |Cite
|
Sign up to set email alerts
|

Are thermodynamic cycles necessary for continuum solvent calculation of pKas and reduction potentials?

Abstract: Continuum solvent calculations of pKas and reduction potentials usually entail the use of a thermodynamic cycle to express the reaction free energy in terms of gas phase energies and free energies of solvation. In this work, we present a systematic study comparing the solution phase free energy changes obtained in this manner with those directly computed within the SMD solvation model against a large test set of 117 pKas and 42 reduction potentials in water and DMSO. The inclusion of vibrational contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
215
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(222 citation statements)
references
References 86 publications
7
215
0
Order By: Relevance
“…Results (Supporting Information Tables S8 andS9, Figs. S3–S6) showed solvation models played an important role in the computations of reduction potentials and SMD and IEFPCM‐Bondi models produced better results compared to IEFPCM‐Pauling model, which was in agreement with Ho's conclusion on the solvation model based on the computed results of the 117 p K a 's and 42 reduction potentials of the nontransition metal‐containing molecules …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Results (Supporting Information Tables S8 andS9, Figs. S3–S6) showed solvation models played an important role in the computations of reduction potentials and SMD and IEFPCM‐Bondi models produced better results compared to IEFPCM‐Pauling model, which was in agreement with Ho's conclusion on the solvation model based on the computed results of the 117 p K a 's and 42 reduction potentials of the nontransition metal‐containing molecules …”
Section: Resultssupporting
confidence: 80%
“…Density functional theory (DFT) has proven to be a reliable, convenient, and advantageous tool for computing reduction potentials . Although many studies have utilized DFT, the absolute deviations between the experimental data and computed values are still quite large for some transition metal‐containing complexes (including both inorganic and organometallic complexes) compared with simple organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…With this partitioning scheme, however, free energies cannot be straightforwardly calculated because vibrational modes cannot (easily) be attributed to the solute and its direct surrounding (see also the recent comparison of finite‐temperature models for solution in Reference and references therein). We note that a recent study showed that the inclusion of vibrational contributions in the free energy of solvation can have a negligible effect on the accuracy of thermodynamic cycle predictions of pK a 's and reduction potentials.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigations have been performed to determine the solvation energies of the proton in water . Besides, only few authors have been interested in the solvation energies of the proton in other solvents such as methanol, acetonitrile, dimethyl sulfoxide, acetone, benzene, ethanol, and ammonia .…”
Section: Introductionmentioning
confidence: 99%